1921
DOI: 10.1002/jez.1400330108
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen supply of certain animals living in water containing no dissolved oxygen

Abstract: Sobre la adquisicidn del odgeno por ciertos animales que viven en el agua desprovista de oxigeno disuelto.Birge y Juday han demostrado que durante una parte del afio el agua del fondo del lago Mendota estli desprovista de oxigeno disuelto, a pesar de lo cual ciertos animales continGan viviendo, aGn durante este periodo. El problenia de la adquisicidn de oxigeno por estos habitantes (particularmente las larvas de Chironomus tentans) durante el periodo de estancaniiento ha sido objeto de estudio por el autor, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1931
1931
1974
1974

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Finally, Cole (1921) claimed that decomposing plant tissues give off small amounts of atomic oxygen even under anaerobiosis and that many invertebrates are able to use this. If this is true, then quite significant amounts of oxygen could be produced in the substrate from the large quantities of plant detritus trapped there.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Cole (1921) claimed that decomposing plant tissues give off small amounts of atomic oxygen even under anaerobiosis and that many invertebrates are able to use this. If this is true, then quite significant amounts of oxygen could be produced in the substrate from the large quantities of plant detritus trapped there.…”
Section: Discussionmentioning
confidence: 99%
“…Portier (1911) suggested that in the larva of Hydrocampa there was a symbiotic relation between the insect and the green leaves composing its case, but Ege (1926) considers this idea untenable and shows that the larva aerates its case chiefly by fetching air from the atmosphere. Cole (1921) found Chironomus larvae at the bottom of lakes, in an environment where no oxygen could be detected. He discusses at length the question of their oxygen supply and suggests that perhaps the decomposition of plant tissues may provide a source of oxygen in atomic form.…”
Section: Aquatic Plants As a Source Of Oxygenmentioning
confidence: 99%
“…How the many animals which live and remain active in bottom muds for long periods without oxygen carry on metabolism is still somewhat of a mystery. Cole (1921) believes that decomposing plant remains may liberate an oxidizing substance which can supply oxygen to bottom animals. Perhaps certain profundal bottom animals are not only able to live without oxygen but are also capable of subsisting on dissolved or colloidal organic food (Hinman 1930).…”
Section: Ecology Of Lake Fishes By a S Pearse Duke Universitymentioning
confidence: 99%
“…How the many animals which live and remain active in bottom muds for long periods without oxygen carry on metabolism is still somewhat of a mystery. Cole ( 1921) believes that decomposing plant remains may liberate an oxidizing substance which can supply oxygen to bottom animals. Perhaps certain profunda!…”
mentioning
confidence: 99%